PENGARUH PROPOLIS TERHADAP SEKRESI INTERLEUKIN-12 PADA SUPERNATAN KULTUR MAKROFAG DARI PENDERITA TUBERKULOSIS PARU YANG DIINFEKSI Mycobacterium tuberculosis - Linawati, Made; Bagiada, Made (journal of internal medicine; Vol. 10, No. 1 Januari 2009)
The uses of adjuvan imunotherapy has attract the attention tuberculosis treatment, because of the increasing patient persentage in antituberculosis agent. Propolis is bee glue, contain of caffeic acid phenethyl ester (CAPE) that assume immunomodulator activities. The aim of this study were to assess the role of propolis to interleukin 12 secretion in macrophages culture from pulmonary tuberculosis patient that infected with Mycobacterium tuberculosis (M tb). This study was true experimental using post test only control group design, with sampel from peripheral blood mononuclear cells (PBMC) of lung tuberculosis patient that divided into 3 groups within 6 replication. Group I as control group without M tb infection and propolis intervention; group II treatment group with M tb infection only; and group III treatment with M tb infection and propolis intervention. Interleukin 12 secretion were measured 48 hours post M.tb infection. Result showed that means of interleukin 12 secretion at these groups are 11 pg/ml; 23.33 pg/ml; 37 pg/ml in which intervention of propolis 10 mg/ml before M tb infection could increase interleukin 12 consentration significanly (p< 0.05) compared with control group and group with infection of M tb only. We conclude that propolis could increases macrophages activities with in increase secretion of interleukin 12.
Keywords: interleukin 12 secretion, propolis, macrophages culture from lung tuberculosis patient